Heideggerian meanings and senses of institutionalized depressive elderly: implications for nursing (Research, Society and Development, 2023)
Objectives: to understand the meanings, reveal the meanings of being elderly with depression and describe the role of the nursing team revealed by the elderly. Methodology: Qualitative research with Martin Heidegger's phenomenological approach carried out with 07 institutionalized depressive elderly aged over 60 years. A phenomenological interview was carried out and the testimonies were faithfully transcribed and carefully read in order to search for the being of these elderly people. Meaning units, vague and median understanding and interpretive analysis were constituted. Results: Being an elderly person depressed meant: being afraid, feeling sad, wanting to cry and leave and feeling abandoned; taking medication, being treated for depression and being healthy. Depression in the elderly is more evident due to the fact that they are aging and having to live with illnesses that are aggravated by depression. Final considerations: Early diagnosis and adequate treatment are needed in addition to the use of medication for depression. The reality of life of the elderly must be taken into account and nursing professionals, together with the multidisciplinary team, need to promote not only physical comfort, prioritize the treatment of depression, seek support from family members, identify problems early and establish the best plan of care, exercising qualified assistance in an integral way. The research also contributed for new studies to be carried out considering gerontological care, since many professionals, especially nurses, who provide care in these institutions have generalist training.